1966
DOI: 10.1021/bi00865a008
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of Certain Proteins from the Human Erythrocyte Stroma*

Abstract: This material was taken in part from the thesis submitted by Carolyn D. Mitchell in partial fulfillment of the requirements for the degree of Doctor of Philosophy, University of Washington, 1965. 1 "Stroma" refers to the post-hemolytic residue or "ghosts," usually considered to be representative of the surface structure of the erythrocyte. ments have been formed. Ultracentrifugation of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1971
1971
1972
1972

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Stroma prepared with added MgCI, was treated with 1.2 M NaCl solution as described by Mitchell and Hanahan [7]. Aliquots of the supernatant solutions were dialyzed a t 4 "C against distilled water and lyophilized; lipids were extracted from the lyophilized residues.…”
Section: Solubilization With Hypertonic Salinementioning
confidence: 99%
See 3 more Smart Citations
“…Stroma prepared with added MgCI, was treated with 1.2 M NaCl solution as described by Mitchell and Hanahan [7]. Aliquots of the supernatant solutions were dialyzed a t 4 "C against distilled water and lyophilized; lipids were extracted from the lyophilized residues.…”
Section: Solubilization With Hypertonic Salinementioning
confidence: 99%
“…Investigations of Dodge et al [3] and Mitchell et al [7] have shown that human erythrocytes do not yield intact "ghosts" unless certain precautions are taken during the hemolysis procedure. Hemolysis of human erythrocytes in hypotonic buffers of 20-25 mosM and pH > 7.0 and subsequent washings yield ghosts that are essentially free of hemoglobin and retain virtually all of their membrane constituents, including acetylcholinesterase activity.…”
Section: Effect Of Magnesium Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that this soluble material may be associated with lipid or other protein [ 1,4,5] . Acetylcholinesterase has also been solubilised as a lipoprotein by washing erythrocytes with 1.2 M sodium chloride [6]. Accordingly, the effect of phospholipase A on the acetylcholinesterase solubilised by Triton Xl00 treatment of erythrocyte membranes has been investigated.…”
Section: Introduction the Effect Of Phospholipase A On Human Erythrocmentioning
confidence: 99%